Reduced intensity allogeneic stem cell transplant with anti‐thymocyte globulin and post‐transplant cyclophosphamide in acute myeloid leukemia. (9th September 2019) - Salas, Maria Queralt; Prem, Shruti; Atenafu, Eshetu G.; Law, Arjun Datt; Lam, Wilson; Al‐Shaibani, Zeyad; Loach, David; Kim, Dennis (Dong Hwan); Michelis, Fotios V.; Lipton, Jeffrey Howard; Kumar, Rajat; Mattsson, Jonas; et al.
Abstract: Objectives: We aimed to study the efficacy of reduced intensity conditioning (RIC) allo‐HSCT combined with anti‐thymocyte globulin (ATG) and post‐transplant cyclophosphamide (PTCy) for graft‐versus‐host disease (GVHD) prophylaxis in AML. Methods: One hundred forty‐seven patients were included. All patients underwent unmanipulated peripheral blood stem cell RIC allo‐HSCT. Median follow‐up was 12.8 months (range 0.5‐39). Results: Median age was 58 years. Twenty‐nine (20%) recipients received 10/10 MRD grafts, 69 (47%) 10/10 MUD grafts, 20 (13.6%) 9/10 MMUD, and 29 (20%) haploidentical grafts. The cumulative incidence of grade II‐IV and III‐IV acute GVHD at day +100, and moderate/severe chronic GVHD at 1‐year were as follow: 14.3%, 1.4%, and 8.3%. There were no significant differences according to donor type ( P  = .46) and cumulative incidence of GVHD. One‐year overall survival (OS), relapse‐free survival (RFS), non‐relapse mortality, and GVHD‐free/Relapse‐free survival were as follows: 66.9% (95% CI 58.4‐74), 59.9%, and 18.7% and 53.7%. KPS ≤ 80 was predictive of worst OS ( P  = .04). Those recipients who received MUD transplants had better RFS ( P  = .01). Conclusions: RIC allo‐HSCT combined with ATG and PTCy is safe and a potentially curative strategy and it is associated with impressive GRFS in AML.